Network Effects and Trust in Malaysia’s Platform Economy - Kurniawan Arif Maspul; Muhammad Ardhin (Journal of Business Management, 2025)
The rapid proliferation of platform business models has fundamentally reshaped global economies, with network effects and institutional legitimacy emerging as cornerstones of sustainable platform dominance. This study explores how these two forces interact to influence platform scalability, regulatory acceptance, and long-term market entrenchment, using Malaysia’s platform economy—with a particular focus on Grab—as a case study. Through a multi-theoretical approach, integrating institutional theory, platform economics, and behavioral economics, this research applies a PESTLE framework to dissect the socio-political, economic, and technological forces shaping platform sustainability. Empirical analysis of regulatory policies, market reports, and consumer behavior data illustrates how Grab’s strategic regulatory engagement, cultural adaptation, and gig labor policies contributed to its dominance, while Uber’s inability to navigate Malaysia’s socio-political landscape led to its exit. The study underscores the synergistic relationship between network externalities and regulatory legitimacy, arguing that sustainable platform leadership necessitates not only technological innovation but also deep-rooted institutional agility and cultural intelligence.